STUDYING FANDOM ONLINE: A CASE STUDY OF TWICE AND STRAY KIDS FANDOM ON FAN FICTION PRACTICES OF @ESKALOKAL AND @GABENERTWICE ON TWITTER - Cendera Rizky Bangun; Nareswari Kumaralalita; Gabriela Frederika Febe Sukur (ASPIKOM Jabodetabek Region, 2020)
Popular culture is developing over time and fanfiction is product of popular culture. Fanfiction is a work of fiction created by fans as a sense of involvement (a culture of participation) between them and their idols. In addition to creating a sense of